(untitled) - Ali, Moi (London, 2001)
Learn all you need to know about how to generate and manage publicity - from recognising public relations opportunities to creating and sustaining media coverage. "Effective Public Relations" not only shows you how to identify and target your audience but also provides practical techniques for presenting information whether writing news releases or organising press conferences and product launches. This title features power tips that help you to deal with real-life situations and handle all types of media with confidence.
Keywords: Public relations